Differential degradation of petroleum hydrocarbons by Shewanella putrefaciens under aerobic and anaerobic conditions - Li, Yang; Liu, Yuan; Guo, Dongyi; Dong, Hailiang (Frontiers in Microbiology, 2024)
The complexity of crude oil composition, combined with the fluctuating oxygen level in contaminated environments, poses challenges for the bioremediation of oil pollutants, because of compound-specific microbial degradation of petroleum hydrocarbons under certain conditions. As a result, facultative bacteria capable of breaking down petroleum hydrocarbons under both aerobic and anaerobic conditions are presumably effective, however, this hypothesis has not been directly tested. In the current investigation, Shewanella putrefaciens CN32, a facultative anaerobic bacterium, was used to degrade petroleum hydrocarbons aerobically (using O2 as an electron acceptor) and anaerobically (using Fe(III) as an electron acceptor). Under aerobic conditions, CN32 degraded more saturates (65.65 ± 0.01%) than aromatics (43.86 ± 0.03%), with the following order of degradation: dibenzofurans > n-alkanes > biphenyls > fluorenes > naphthalenes > alkylcyclohexanes > dibenzothiophenes > phenanthrenes. In contrast, under anaerobic conditions, CN32 exhibited a higher degradation of aromatics (53.94 ± 0.02%) than saturates (23.36 ± 0.01%), with the following order of degradation: dibenzofurans > fluorenes > biphenyls > naphthalenes > dibenzothiophenes > phenanthrenes > n-alkanes > alkylcyclohexanes. The upregulation of 4-hydroxy-3-polyprenylbenzoate decarboxylase (ubiD), which plays a crucial role in breaking down resistant aromatic compounds, was correlated with the anaerobic degradation of aromatics. At the molecular level, CN32 exhibited a higher efficiency in degrading n-alkanes with low and high carbon numbers relative to those with medium carbon chain lengths. In addition, the degradation of polycyclic aromatic hydrocarbons (PAHs) under both aerobic and anaerobic conditions became increasingly difficult with increased numbers of benzene rings and methyl groups. This study offers a potential solution for the development of targeted remediation of pollutants under oscillating redox conditions.